Peran “Nyai” dalam Meningkatkan Mutu Pendidikan Pesantren di Pondok Pesantren Nurut Taqwa Sangkapura Bawean Gresik - Nurdiana, Defi Dachlian (International Conference on Islamic Studies, 2020)
Nyai's role as one of the leaders in the Nurut Taqwa Islamic Boarding School as a source of exemplary religious attitudes and knowledge in the pesantren has a strategic role. Facing social changes due to modernization that entered the era of the industrial revolution 4.0, there are big challenges for Islamic boarding schools that are required to be able to respond to these social changes. For this reason, improving the quality of pesantren education needs to be made with proper planning, in order to be able to produce quality pesantren education. The focus of this research is to examine the role of Nyai in improving the quality of education at the Nurut Taqwa Sangkapura Islamic Boarding School. This research is a qualitative case study with data collection by observation, interviews and documentation. The results showed that (1) there were two focuses on the quality of education in the Nurut Taqwa Islamic boarding school, namely the quality of the human resources of the santri’s and the quality of the pesantren institutions. (2) Nyai's role in quality improvement through the planning, implementation, control and evaluation processes. (3) Nyai leadership type is more dominant to democracy and charismatic.